2018
DOI: 10.1002/brb3.1176
|View full text |Cite
|
Sign up to set email alerts
|

Relation of postoperative serum S100A12 levels to delirium and cognitive dysfunction occurring after hip fracture surgery in elderly patients

Abstract: ObjectiveBrain injury is implicated in pathogenesis of postoperative delirium (POD) and cognitive dysfunction (POCD). S100A12 is involved in inflammatory process and is recently known as a biomarker for brain injury. Herein, we clarified whether serum S100A12 levels are related to POD and POCD after hip fracture surgery in elderly patients.Materials and MethodsIn this prospective, observational study, we gauged S100A12 levels in preoperative and postoperative serum from 186 patients and serum from 186 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Preoperative hypoalbuminemia directly affects the pharmacological effects of anesthetic drugs, resulting in uncertainty in the dose selection and duration of action, which can directly or indirectly affect postoperative neural function[ 32 ]. Consistent with previous reports[ 33 , 34 ], this study also confirms that preoperative hypoproteinemia is associated with postoperative delirium. This result shows that actively correcting preoperative hypoproteinemia is of great significance for the prevention and treatment of postoperative delirium in patients with hip fracture.…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative hypoalbuminemia directly affects the pharmacological effects of anesthetic drugs, resulting in uncertainty in the dose selection and duration of action, which can directly or indirectly affect postoperative neural function[ 32 ]. Consistent with previous reports[ 33 , 34 ], this study also confirms that preoperative hypoproteinemia is associated with postoperative delirium. This result shows that actively correcting preoperative hypoproteinemia is of great significance for the prevention and treatment of postoperative delirium in patients with hip fracture.…”
Section: Discussionsupporting
confidence: 93%
“…27 In a prospective, observational study of 186 patients and 186 controls, a postoperative elevation of serum S100A12 levels was independently correlated with serum C-reactive protein levels after hip fracture surgery in elderly patients. 28 Another clinical study showed that serum S100A12 levels were substantially higher in patients with severe traumatic brain injury than in healthy controls; and serum concentrations of S100A12 significantly correlated with admission serum concentrations of C-reactive protein, interleukin-6 and tumor necrosis factor-alpha. 11 In patients with ICH, enhanced serum S100A12 levels were positively correlated with blood glucose concentrations, blood white blood cell count and plasma C-reactive protein concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative serum S100A12 levels were independently associated with the risk of developing postoperative delirium and cognitive dysfunction in a group of elderly patients undergoing hip fracture surgery. 28 In patients with acute ICH or severe traumatic brain injury, serum S100A12 levels independently predicted 30-mortality and overall survival. 11,12 In particular, plasma S100A12 emerged as an independent predictor for a poor functional outcome after acute ischemic stroke.…”
mentioning
confidence: 99%
“…Severe neuroinflammation may be a main cause of POD in patients undergoing cardiac or non-cardiac surgery ( 38 , 39 ). The serum S100A2 is a pro-inflammatory factor associated with POD and also a biomarker indicating neural injury according to a clinical study, and maybe an effective predictor of POD ( 40 ). Increasing perioperative plasma cortical level is considered as another mechanism of POD occurrence due to its related neuron apoptosis in the hippocampal region ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%